Učne priprave na nastope bodočih učiteljev - Magajna, Zlatan; Umek, Maja (Revija za elementarno izobraževanje, 2019)
Prospective teachers’ lesson plans. Prospective teachers and pedagogical educators at all levels and in all types types of schools in Slovenia occasionally prepare lessons under the supervision of university staff and execute them in educational institutions. In the academic year 2016/17, we conducted an empirical study among the university teachers of special didactics at the Faculty of Education at the University of Ljubljana about student lesson plans in such an activity. We considered good practices developed within special didactics and compared these with current international trends. The research serves as a basis for improving the quality use of lesson plans in the professional development of prospective teachers.